Design of a Flexible Pavement For Nyakabande–Mutolere Road, Nyakabande Sub County, Kisoro District. - Habimana, Stephen (Kabale University, 2023)
Transport remains a vital factor for the social, economic and political well-being of any nation and it is thus of paramount importance. Besides the 94% of road accidents being caused by human error, poor driving road surfaces which result from inadequate and premature pavement deteriorations, are responsible for various accident reports in the country, Uganda. This study intended to provide a suitable pavement design for Nyakabande – Mutolere link, which is about 2.0km and forms a quickest link between Nyakabande and Mutolere trading centres in Kisoro District. The design was limited to flexible pavement since it is the commonest pavement structure used on almost all the countryside roads. The study commenced with traffic studies analysis which indicated a traffic class category T5 for a design life of 20 years with a cumulative standard axle in millions of 3.52. The subgrade investigation of the areas gave a 6.5% as the 10th percentile CBR, which was used as the design CBR for the study, giving a subgrade class, S3. The climate analysis of area indicates a wet condition with 8 and 4 months in rainy and dry seasons respectively. These inputs were then used together with the design catalogues from MoWT Pavement Design Manual to select pavement layers. The selected pavement structures from the design catalogues were then analysed using RUBICON Pavement analysis software to ascertain their suitability. It was later found that a pavement structure with a surfacing thickness of 50mm, CRR Base of 200mm, G45 Subbase of 250mm, and a capping layer of 200mm was satisfactory for the design requirements. This Optimum pavement structure upon analysis indicated ability to serve up to 21.5 years before indicating signs of failure, according to results from the software. It was thus recommended to adopt this pavement structure for Nyakabande - Mutolere Road link.